KOMPARASI DETERMINAN BELANJA PEMERINTAH ANTARA DAERAH PEMEKARAN DAN TIDAK DI PULAU SUMATERA, INDONESIA - Roosemarina Anggraini Rambe (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
This study aims to examine the role of previous year’s tax, revenue sharing, GRDP, population, and the dummy of district status toward the local government spending in Sumatra. Tuliskan jenis/disain peneltian yang digunakan, variable yang digunakan serta struktur data yang digunakan. The study is explanatory research. The study applies the data panel regression technique. Data used is panel data of districts/cities in Sumatra from 2008 to 2019. Results show that the role of the previous year's tax, GRDP, population toward the local government spending significantly affects the local government spending of splitting and non-splitting regions. For a dummy of district status, district's government spendings are higher than those of cities’s government spendings. For splitting regions, the previous year’s tax has the strongest impact on local government spending, followed by the dummy variable of district status. Revenue sharing does not influence local government spending. For non-splitting regions, the dummy variable of district status has the biggest impact on local government spending, followed by the previous year’s tax. Revenue sharing positively influences local government spending. The study recommends that local governments encourage the growth of the business sector and manage tax revenue by implementing intensive taxation.